Comparative Antimicrobial Activity of Areca catechu Nut Extracts using Different Extracting Solvents - Rahman, M Arifur; Sultana, Papeya; Islam, M Sahidul; Mahmud, M Toslim; Rashid, M Mamun Or; Hossen, Foysal (Bangladesh Journal of Microbiology, 2016)
Scientists from different sectors are investigating plants for their antimicrobial usefulness. Studies have found thousands of plants which have inhibitory effects on a range of microorganisms in vitro. Surprisingly, only around 10% of all the plants have been investigated in this purpose. The antimicrobial properties of Areca catechu nut extract has been reported earlier. In our study, we have observed and compared the antibacterial activity among n-hexane, ethanol and water extract of A. catechu nut. We found antimicrobial effect only from ethanol and water extract. On the contrary, there was no antibacterial effect observed from n-hexane extract. Furthermore, the extracts are effective only against gram positive bacteria. The ethanol extract concentration from 0.188-0.377 mg/ml was the minimum inhibitory concentration (MIC) for gram positive bacteria used in our study. While, minimum bactericidal concentrations (MBC) were 0.377-0.753 mg/ml for this group of microorganisms. On the other hand, in case of water extract the MIC and MBC were 0.047-1.56 and 0.094-3.125 mg/ml respectively for Gram-positive organisms. This study suggest that A. catechu nut extract can be a potential source for developing antibacterial agents against Gram-positive bacteria which are commonly found on human oral cavity and responsible for dental caries. Bangladesh J Microbiol, Volume 31, Number 1-2,June-Dec 2014, pp 19-23